2010
DOI: 10.1002/ange.200905967
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature CH Activation and Cross‐Coupling of Aryl Ureas in Water

Abstract: Nur mischen und umrühren: Pd‐katalysierte C‐H‐Aktivierungen/Kreuzkupplungen können bei Raumtemperatur in Wasser/Tensid‐Mischungen ausgeführt werden. Unter micellarer Katalyse vermittelt ein System aus Pd(OAc)2 und HBF4 die Reaktion von Arylharnstoffen mit Aryliodiden unter sehr milden Bedingungen (siehe Schema). Die katalytisch aktive Spezies ist ein in situ gebildeter, kationischer Palladiumkatalysator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In summary, a novel palladium(II)-catalyzed ortho-chlorination/bromination reaction has been developed for the synthesis of a broad range of arene chlorides from easily accessible electron-deficient arenes. It was found that both the co-oxidant and TfOH [17] serve as critical factors for regioand chemoselective CÀH activation. A preliminary evaluation of relative DG abilities was conducted to provide some insight into the priority ordering of DG abilities.…”
mentioning
confidence: 99%
“…In summary, a novel palladium(II)-catalyzed ortho-chlorination/bromination reaction has been developed for the synthesis of a broad range of arene chlorides from easily accessible electron-deficient arenes. It was found that both the co-oxidant and TfOH [17] serve as critical factors for regioand chemoselective CÀH activation. A preliminary evaluation of relative DG abilities was conducted to provide some insight into the priority ordering of DG abilities.…”
mentioning
confidence: 99%
“…It was found that both the co-oxidant and TfOH [17] serve as critical factors for regioand chemoselective CÀH activation. It was found that both the co-oxidant and TfOH [17] serve as critical factors for regioand chemoselective CÀH activation.…”
mentioning
confidence: 99%
“…However, only a handful of methodologies for the direct CH arylation of arenes and heteroarenes in which water is used as the only solvent have been reported 4. Despite the high levels of interest in developing mild CH arylation reactions, only one room temperature CH activation and aryl cross‐coupling reaction in neat water has been reported, albeit requiring the use of surfactants and super‐stoichiometric amounts of the strong acid HBF 4 4f. We now report that the direct arylation of indoles with iodoarenes can be achieved at room temperature and “on water” by using a carefully chosen Ag‐carboxylate salt as the base in the reaction.…”
Section: Methodsmentioning
confidence: 93%